Description Metacognition Skills in Academic Ability inHigh and Low Academic College Biology Education - Elok Nur Faiqoh; Suratno Suratno; Yushardi Yushardi (The Faculty of Teacher Training and Education The University of Jember Jember, Indonesia, 2017)
Metacognition is a high-level thinking skill of thinking as to which should be thinking in order to develop a strategy to solve the problem. In the end, a college has different learning styles, causing differences in metacognition skills in each college, including solving a problem in learning. The purpose of this study is to describe differences in metacognition skills in the 6th-semester college at different academic abilities. Type of. Research that used in this research is descriptive qualitative. Subject’s research is students of Biology Education in 6th semesters. This study uses inventory with Metacognitive Awareness Inventory (MAI), which was adapted from Schraw, G & Dennison, R.S. Results of research showed a variation on metacognition skills in the 6th-semester college of biology education at different levels of academic ability